IN VITRO PRESERVATION OF POTATO PLANTS - Strzelczyk-Żyta, Danuta (Plant Breeding and Seed Science, 2017)
Potato plants free of viruses, bacteria and viroid could be maintained in vitro for a long time. Proper prepa-ration of potato plants for in vitro culture provide its long-term storage in good condition. First step is to es-tablish in vitro culture from young greenhouse grown plants in early developmental stage. Explants are main-tained and propagated by nodal subculture on hormone-free Murashige and Skoog (MS) medium at tempera-ture 20-22°C. After rooting, for longer preservation plants are maintained at temperature 8-10°C.